2023
DOI: 10.3389/fmars.2023.1268348
|View full text |Cite
|
Sign up to set email alerts
|

Tidal energy extraction modifies tidal asymmetry and transport in a shallow, well-mixed estuary

Preston Spicer,
Zhaoqing Yang,
Taiping Wang
et al.

Abstract: Tidal energy extraction is increasingly being studied as a potential renewable energy resource in estuaries worldwide. Although it is understood that energy extraction via tidal stream turbines can modify currents and transport within estuaries, it is not clear how the underlying nonlinear physical mechanisms dictating tidal hydrodynamics are modulated. This research investigates the influence of a hypothetical tidal stream turbine array on barotropic tidal processes in a shallow, well-mixed system: the Piscat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Less habitat for these species could harm the shell fishing industry as well as the broader food web of the region supported by eelgrass. A recent study analyzing the effects of tidal energy extraction in a tide dominated estuary estimated a ∼10% decline in intertidal area was possible with an analogous tidal range decrease of ∼20 cm (Spicer et al., 2023). Similarly, we expect a reduction in the transport of water into and out of South Sound.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Less habitat for these species could harm the shell fishing industry as well as the broader food web of the region supported by eelgrass. A recent study analyzing the effects of tidal energy extraction in a tide dominated estuary estimated a ∼10% decline in intertidal area was possible with an analogous tidal range decrease of ∼20 cm (Spicer et al., 2023). Similarly, we expect a reduction in the transport of water into and out of South Sound.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, C e is directly prescribed as a constant 0.5 as we are not modeling any specific turbine design, but rather approximating the effect of generic turbines (e.g., Spicer et al, 2023;Yang et al, 2013). In iterative curvefitting tests between modeled and observed turbine velocity profiles, Li et al (2017) found C e of 0.41 to match observations best, and so a similar value is used here.…”
Section: Tidal Model and Energy Extraction Setupmentioning
confidence: 99%
See 3 more Smart Citations